The Birth of "Arrow of Time" Scientific Knowledge - Kravchenko, Sergey A. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
This article analyzes the consequences of ‘arrow of time’ expressed in the becoming complex socium that are seen as new challenges for the existing knowledge. The author argues that the effect of ‘arrow of time’ should be extended to the non-linear dynamics of scientific knowledge in general and sociological knowledge in particular, stating that the ‘arrow of time’ scientific knowledge is being born and it is based on new synthesis of sciences. In this regard, there analyzed the ‘turns in sociology’ – qualitative changes in its interaction with other sciences borrowing their knowledge - as separate terms as well as concepts which are then filled with the actual sociological content. The answer to these encountered challenges the author sees in humanistic turn involving a synthesis of social, hard and humane sciences and their development in the direction of searching for new forms of humanism based on men’s existential needs.